2021
DOI: 10.1371/journal.pone.0252939
|View full text |Cite
|
Sign up to set email alerts
|

Blood coagulation parameter abnormalities in hospitalized patients with confirmed COVID-19 in Ethiopia

Abstract: Background Coagulopathy and thromboembolic events are among the complications of Corona Virus disease 2019 (COVID-19). Abnormal coagulation parameters in COVID-19 patients are important prognostic factors of disease severity. The aim of this study was to analyze coagulation profiles of hospitalized COVID-19 patients in Addis Ababa, Ethiopia. Methods This prospective cross-sectional study was conducted among 455 Covid-19 patients admitted at Millennium COVID-19 care and treatment center, Addis Ababa, Ethiopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
(60 reference statements)
3
22
0
Order By: Relevance
“…In our study, aPTT was the parameter with the highest prediction of mortality in COVID-19 patients, with an AUC of 0.753 and also had a good sensitivity and the highest specificity (92%). In addition, consistent with our findings, several studies showed that aPTT was significantly longer in non-surviving COVID-19 patients [ 15 , 16 , 17 ]. The second most significant parameter in the mortality of COVID-19 patients from our study is D-dimer, which showed a good performance with an AUC of 0.751.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, aPTT was the parameter with the highest prediction of mortality in COVID-19 patients, with an AUC of 0.753 and also had a good sensitivity and the highest specificity (92%). In addition, consistent with our findings, several studies showed that aPTT was significantly longer in non-surviving COVID-19 patients [ 15 , 16 , 17 ]. The second most significant parameter in the mortality of COVID-19 patients from our study is D-dimer, which showed a good performance with an AUC of 0.751.…”
Section: Discussionsupporting
confidence: 93%
“…Prolonged PT and elevated PT/INR (international normalized ratio) were detected significantly more often in deceased and ICU admitted children. In line with previous studies in adults and children (40,41), the correlation between coagulation irregularities and the disease severity was confirmed, indicating that liver dysfunction can be used as a marker for predicting the severity of COVID-19 in children (42). In this study, a tendency for increased severity was seen among cases with elevated AST, similar to results from a meta-analysis (43).…”
Section: Discussionsupporting
confidence: 91%
“…Although the most common pattern of coagulopathy observed in patients hospitalized with COVID-19 is characterized by elevations in fibrinogen and D-dimer levels and mild prolongation of PT/aPTT [ 11 ], some previous studies showed that the coagulopathy in patients hospitalized with COVID-19 is characterized by increase in INR too. A prospective cross-sectional study was conducted among 455 COVID-19 patients admitted at the COVID-19 care and treatment center, Ethiopia, from July 1 to October 23, 2020, which showed that prolonged INR was more frequent among severe and critical COVID-19 patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%